Protection status of the Sami identity in Finland in the first years after accession - Kaczmarek, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Sami people are the only native people in Europe. Their identity and culture are related to the nature of the northern part of the Scandinavian peninsula. Due to the difficult natural conditions occurring there, the Saami identity is subject to special protection both in Finland and in the European Union. The activities of external institutions mainly consist in multi-faceted activities aimed at improving the quality of life in those areas and counteracting the depopulation of regions traditionally inhabited by the Sami people.
Keywords: Finland; Sami people; cultural identity; EU funds